The Role Communication Technology in Enhancing Student Collaboration for Da'wah - Akbar, M. Fikri; Aziz Apriadi, Eko; Aini, Fitaha (Fakultas Ushuluddin Adab dan Dakwah IAIN Metro-Lampung, 2024)
This study examines the role of communication technology in enhancing collaboration among Public Relations and Digital Communication students at Sang Bumi Ruwa Jurai University, particularly in supporting da'wah and promoting Islamic values. Using a qualitative case study approach with ten purposively selected participants, data was collected through in-depth interviews and observations, analyzed thematically. Findings highlight the significant role of technologies like Zoom, Google Meet, WhatsApp, and Google Drive in improving collaboration efficiency and flexibility, enabling real-time discussions and overcoming time and location barriers in da'wah contexts. However, challenges such as technical issues and difficulty building virtual interpersonal relationships were noted. The study recommends improving technology access, technical training, and supportive policies to optimize technology use in collaborative da'wah activities. These insights inform strategies for developing technology-based learning in higher education, particularly in Islamic communication, equipping students with essential skills for the digital era.